2011
DOI: 10.1074/jbc.m110.216028
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Glutathione Peroxidase 4 Expression during Enterocytic Cell Differentiation

Abstract: Glutathione peroxidase 4 (GPx4), an abundant selenoenzyme, is ubiquitously expressed in a tissue-, cell-and differentiationdependent manner, and it is localized in cytoplasmic, mitochondrial, and nuclear cellular compartments. Here, we report cytoplasmic and nuclear localization of GPx4 in Caco-2 intestinal epithelial cells. Enterocytic differentiation of Caco-2 cells triggers an increase in GPx4 mRNA and protein levels, mediated by enhanced promoter activity. We identified a combined cAMP response element (CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…Expression of SBP1 is frequently downregulated in colorectal carcinoma tissue, and low SBP1 expression levels are correlated with poorer patient survival rates, as shown in two independent studies (43,51). Similar to the selenoproteins SeP and GPx4 (82,81), SBP1 levels increase during enterocytic cellular differentiation. Maximal SBP1 expression is observed in terminally differentiated cells of the intestinal epithelium (51).…”
Section: Se-binding Proteinmentioning
confidence: 79%
See 1 more Smart Citation
“…Expression of SBP1 is frequently downregulated in colorectal carcinoma tissue, and low SBP1 expression levels are correlated with poorer patient survival rates, as shown in two independent studies (43,51). Similar to the selenoproteins SeP and GPx4 (82,81), SBP1 levels increase during enterocytic cellular differentiation. Maximal SBP1 expression is observed in terminally differentiated cells of the intestinal epithelium (51).…”
Section: Se-binding Proteinmentioning
confidence: 79%
“…GPx4 is localized in the cytoplasm and nuclei of epithelial cells of the small and large intestine (81). GPx4 might be particularly interesting in regard to Se-dependent chemoprevention, given its nuclear localization and its broad and unique substrate spectrum, including lipid and thymine hydroperoxides.…”
Section: Glutathione Peroxidasesmentioning
confidence: 99%
“…We conclude that in undifferentiated Caco-2 gut epithelial cells changes in GPx4 activity lead to altered AIF expression, which then leads to changes in both the mitochondrial oxidative phosphorylation system and apoptotic signaling. Interestingly, it has recently been observed that GPX4 expression is increased during Caco-2 cell differentiation and that there is higher expression in upper villus enterocytes that are fully differentiated [42]. This suggests that the AIF-related protective role of GPx4 may be particularly important in differentiated enterocytes.…”
Section: Discussionmentioning
confidence: 94%
“…Gpx3, an extracellular Gpx isoform secreted by intestinal cells into the lumen, reportedly participates in protecting the intestinal mucosa against oxidant injury [91]. Gpx4, the only Se-Gpx protein known to reduce phospholipid hydroperoxides, is present in the cytoplasmic and nuclear compartments of human small intestine and colon [92]; interestingly, Se deficiency has no effect on Gpx4 message level or its stability [90]. Pprotein expression and enzymatic activity of Gpx4 are notably increased in differentiated colonocytes in association with enhanced antioxidant protection, especially in the nuclear compartment [92].…”
Section: Redox Balance In the Intestine: Physiological And Pathologicmentioning
confidence: 99%